Predicting Histological Healing and Recurrence in Ulcerative Colitis by Assessing Mucosal Vascular Pattern Under Narrow-Band Imaging Endoscopy - He, Tao; Zong, Lei; Pan, Peng; Sun, Shanming; Qu, Hongmei (Frontiers in Medicine, 2022)
This study investigated the predictive value of narrow-band imaging (NBI) endoscopic staging of different mucosal vascular patterns (MVPs) in patients with ulcerative colitis (UC) for histological healing or clinical recurrence in UC patients. A total of 124 patients with UC in clinical remission attending The First Affiliated Hospital of Weifang Medical College were included in the study and underwent NBI colonoscopy. Inflammatory activity was assessed in the intestine using the Mayo endoscopic score (MES) and the MVP. Mucosal inflammation was histologically graded using the Nancy index (NI). The colons of 124 UC patients were staged according to NBI endoscopic MVP staging criteria. The differences between NBI colonoscopy MVP typing and white light endoscopic MES in assessing histological healing were statistically significant (P < 0.001), and there was a moderate correlation between MES and the degree of histological healing (r = 0.471, P < 0.001). There was also a significant correlation between the severity of mucosal activity determined by white light endoscopy and MVP staging (r = 0.811, P < 0.001). The differences between NBI endoscopic MVP staging and white light endoscopic MES in assessing UC recurrence were statistically significant (P < 0.001). Spearman correlation analysis showed a moderate correlation between NBI endoscopic MVP staging and clinical recurrence. NBI endoscopic MVP staging can predict histological healing and clinical recurrence status better than white light endoscopy.